AN ASSESSMENT OF DRINKING WATER QUALITY IN PRIVATE HOSTELS AROUND UNIVERSITY OF BENIN, BENIN CITY, EDO STATE, NIGERIA - Ibanga, Obot Akpan; EGHAREVBA, Jolly; UBREI-JOE, Maimoni Mariere (REVISTA GEOGRÁFICA ACADÊMICA, 2020)
Livability and comfortability in private hostels in Nigeria to a large extent depend on the quantity and pollution-free water for students’ utilization. A shortfall in quantity and quality of water in the university community and surrounding hostels normally exposes students to various degrees of water stress and other vulnerabilities with serious implications on personal sanitation and hygiene. This paper evaluates drinking water pollution in three private hostels around the University of Benin, Benin City, Edo State, Nigeria. Field-based and laboratory analysis was deployed to investigatethe concentration of 18 water pollutants namely: carbon dioxide, chloride, alkaline, conductivity, pH, hardness, total dissolved solids, total suspended solids, total solids, manganese, calcium, zinc, copper, potassium, cadmium, iron, total aerobic count and coliform.Unacceptable levels of water pollution and quality indicators particularly in copper, cadmium, iron, and coliform were found across the sampled private hostels while other parameters met the World Health Organization limit making the water relatively suitable for consumption.  Besides, there was no spatial variation of water pollution indicators across the sampled private hostels. The need to sustain the concentration of these indicators cannot be over-emphasized to avert water-related diseases that are harmful to the health of man. The paper recommends that students residing at private hostels should cultivate the habits of treating water before consumption using the commonest methods of boiling and filtration to guarantee their health security and wellbeing.